Screening Southeast Asian medicinal plants: Clausena lansium, Leea indica, Strobilanthes crispa, Vitex trifolia for anti-platelet aggregation and blood coagulation effects - Sogand Zareisedehizadeh; Fu-Xun Heng; Chay-Hoon Tan; Paul Chi-Lui Ho; Hwee-Ling Koh (Phytomedicine Plus)
Background: Southeast Asian traditional medicine has long utilized herbs for promoting blood flow and dissolving clots. Four plants - Clausena lansium, Leea indica, Strobilanthes crispa, and Vitex trifolia - have been identified for their potential effects on blood circulation based on traditional use and literature. While these plants exhibit various pharmacological activities, their specific impacts on platelet aggregation and coagulation remain unexplored. Purpose: This study aims to investigate the antiplatelet and anticoagulant activities of extracts from Clausena lansium, Leea indica, Strobilanthes crispa, and Vitex trifolia, bridging traditional medicine with modern research to potentially uncover novel approaches for managing thrombotic disorders. Methods: Aqueous, 70 % ethanolic, and 70 % methanolic extracts were prepared from fresh leaves. Platelet aggregation was analyzed using collagen-induced aggregation in human whole blood. Anticoagulant activities were evaluated by determining the effects on prothrombin time (PT) and activated partial thromboplastin time (aPTT). Results: All Leea indica extracts and the 70 % ethanolic Vitex trifolia extract significantly inhibited platelet aggregation. Clausena lansium extracts promoted platelet aggregation. All extracts prolonged PT and aPTT, with Leea indica and Strobilanthes crispa being most potent. Liquid chromatography and time of flight mass spectrometry (LC-ToF-MS) analysis of Leea indica revealed gallic acid, methyl gallate, epigallocatechin, epigallocatechin-3-O-gallate, and other polyphenolic compounds. These compounds, particularly kaempferol, quercetin, epigallocatechin-3-O-gallate, and β-sitosterol, contribute to Leea indica's potent antiplatelet and anticoagulant effects through multiple mechanisms, including inhibition of platelet activation and various coagulation factors. Conclusions: These findings support the traditional use of Leea indica, Strobilanthes crispa, and Vitex trifolia for improving blood circulation and inhibiting clotting. Leea indica demonstrated remarkable antiplatelet and anticoagulant activities, highlighting its potential in preventing pathological thrombus formation and related cardiovascular disorders.